PENDAMPINGAN DAN PENGUATAN KELEMBAGAAN KELOMPOK SADAR WISATA (POKDARWIS) DI DESA WINDUAJI, KECAMATAN PAGUYANGAN, KABUPATEN BREBES - Chamid Sutikno; Shadu Satwika Wijaya; Zaula Rizqi Atika; Ariesta Amanda; MH Maab (PARADIGMA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Indonesia as country that has geographical diversity, regional characteristics and culture, makes it Indonesia’s potential, especially in the tourism sector. The existence of unique and interisting tourism potential in an area should be utillized through good tourism development. However, the tourism industry in Indonesia is only the stage of development countinues to encourage areas with tourism potential. One of wihich is by promiting the pokdarwis (Kelompok Sadar Wisata) Program. The penjalin reservoir is located in Winduaji village, subdistrict Paguyangan, district Brebes is an icon for the village of Winduaji which ultimately inspires the community to form a tourism awereness group. However, due to limited resources, this pokdarwis Winduaji has not been able to maximize tourism potential properly. Based on this, the presence of community service regarding “Assistance Institutional Strengthening of Tourism Awereness Group (Pokdarwis) in Winduaji Village, Paguyangan Subdistrict, Brebes District” in considered important to carry out.